How Enaction and Ecological Approaches Can Contribute to Sports and Skill Learning - Avilés, Carlos; Navia, José A.; Ruiz-Pérez, Luis-Miguel; Zapatero-Ayuso, Jorge A. (Frontiers in Psychology, 2020)
The purpose of this article is to answer the question of how enactivism and ecological psychology contribute to a better understanding of the process of learning sports skills. This learning process is the product of the interrelationship between many different constraints that are reflected in a particular stage of skill acquisition and performance that each agent or athlete achieves. We will also show the differences and similarities between both post-cognitivist approaches. The first paragraphs on enactivism deal with several key points related to learning, enactive skills, and what it means to be an athlete in action and in situation. The sections on the ecological approach deal with the education of attention, calibration, and the education of intention. We also discuss the importance of representative experimental designs in studies on ecological approach. In the discussion section, we discuss some of the elements that have shaped both approaches, one of them being the methodological circularity that has allowed enactivist researchers to obtain first and third person data. With regard to the rapprochement between enactivists and ecologists, the use of common terms such as affordances conjures up the possibility of a shared future. Finally, we provide a number of general conclusions, one of the most important of which suggests an alliance between enaction and ecological psychology.